Dignified care and associated factors among adult patients admitted to Jimma Medical Center, south west Ethiopia, 2023 - Midhagsaa Dhinsa Kitila; Abiru Neme Negewo; Asresu Feleke Bate; Birhanu Muleta Bayecha; Birhanu Wogane Ilala; Merga garoma Jatu; Misganu Diriba Olana; Mesfin Beharu Deme (BMC Health Services Research)
Abstract Background Dignified care is treating patients as being of worth in a respectful way, considering them as valued individuals. It enhances overall patient well-being, satisfaction, psychological comfort, and confidence. Even though necessary, little is known about dignified care in Ethiopia, particularly in Jimma. Analyzing dignified care helps healthcare providers and program managers to design better strategies. Therefore, this study assesses dignified care and associated factors among adult patients admitted to Jimma Medical Center in Oromia Regional State, southwestern Ethiopia. Methods A facility-based, cross-sectional study design was employed among 422 patients. A simple random sampling technique was utilized to recruit study participants. The magnitude of dignified care was assessed through interviewer-administered structured tools. Binary and multivariable logistic regression was conducted to identify factors associated with dignified care; a P-value < 0.05 at 95% CI was used to declare a statistically significant association. Results The finding revealed that 50.90% (95% CI: 45.97–55.75%) of patients had adequate dignified care. Good care provider-patient relationships [AOR = 2.92; 95% CI (1.79–4.75); p < 0.001], having primary education [AOR = 4.87; 95% CI (1.34–17.76); p = 0.016], being female [AOR = 0.18; 95% CI (0.11–0.30); p < 0.001], living in rural areas [AOR = 0.45; 95% CI (0.21–0.96]; p = 0.049] and being 18–24 years old [AOR = 3.48; 95% CI (1.48–8.15); p = 0.004] were statistically associated with dignified care. Conclusion Nearly half of the study participants received adequate dignified care. Much more is expected from the local administration, healthcare providers, program managers, and community to address the gaps seen in the area of therapeutic relationships, educational level, gender effects, living conditions, and developmental age-related issues, as all of them highly decide the level of dignified care.